Numerical Study of Forced Convective Heat Transfer in Structured Packed Beds of Dimple-Particles. Issue 17 (8th November 2018) - Yang, Jian; Zhou, Lang; Hu, Yingxue; Li, Shiyang; Wang, Qiuwang
ABSTRACT: In this paper, the flow and heat transfer performances inside small pores of structured packed beds of dimple particles are numerically investigated for the first time and some interesting transport phenomena are obtained. Three-dimensional Navier–Stokes equations and SST k-ω turbulence model are adopted for the simulations. The effect of dimple depth is studied in detail, and the flow and heat transfer performances in the packed beds with dimple particles and smooth particles are also compared with each other. It is found that, with the same inlet velocity, the pressure drop and heat transfer in the packed bed with dimple particles would be lower than those in the packed bed with smooth particles, while the overall heat transfer efficiency of packed bed with dimple particles is higher. Furthermore, for the packed bed of dimple particles, the effect of dimple depth is remarkable. With the same inlet velocity, both the pressure drop and heat transfer rate of the packed bed decrease as dimple depth increases, while the overall heat transfer rate is similar for the packed bed with different dimple depths.